Virtual Screening of 8-Gingerol in Zingiber officinale Towards Cox-2 Gene - Bare, Yohanes; S, Mansur; Helvina, Maria; Pili, Aprianus Pani (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Ginger rhizome has polyphenol component which is 8-gingerol. Recent research showed that the compound has role as antiinflammation and antioxidant. This study aim to analyze the role of 8-gingerol which interacts with COX-2. This study used in silico analysis. Protein model COX-2 (ID: 6cox) was taken from Protein Data Bank (PDB) database while 8-gingerol (CID: 168114) from PubChem. Docking and visualization of interaction between COX-2 and 8-gingerol using Discovery Study Client 4.1 software. We found 8-gingerol has the potential as an inhibitor of the COX-2 gene as evidenced by the 3 amino acid residues that interact with the ligands on the active site and are supported by van der Waals forces and a bond energy of -340.3 cal/mol.